EFEKTIVITAS PELAYANAN SATUAN LAYANAN KEPENDUDUKAN DAN PENCATATAN SIPIL PRIMA - Anggarwati, Aryn Putri; Sagita, Novie Indrawati; Taryana, Agus (Jurnal Governansi, 2024)
The most important indicator of successful government performance is public services. Specifically, in population administration services, people often face the most complicated bureaucratic procedures, lengthy, and wasting time. This situation creates opportunities for certain individuals to offer alternative bureaucratic paths for an additional fee and as we know that’s corrupt. This phenomenon reduces trust in the government and lowers the quality of population administration and civil registration services. To improve services, there is a need for the simplification of procedures, clarity, and easy access. The central government has authorized local governments to innovate, including in Depok City through the Sanpel De Prima program. This program was launched to bring services closer to the community and enhance public satisfaction with easy, affordable, fast services. This research aims to examine the effectiveness of population services in increasing public satisfaction and encouraging the ownership of population documents. This study uses qualitative research methods to evaluate the effectiveness of the Sanpel De Prima service. Despite this, there are still various issues hindering its effectiveness, such as lack of transparency in the status of document submissions, minimal program socialization, insufficient human resources, and incompetence of existing personnel. To measure the level of effectiveness, this research uses the effectiveness theory by Budiani, which involves variables such as Target Accuracy, Program Socialization, Purposes, and Monitoring Program to determine the program's effectiveness. Overall, the result of the program's implementation has shown its effectiveness, although there are some inhibiting factors from the internal side of the apparatus, infrastructure, and the community itself. Additionally, steps towards improvement are being aligned to better meet public satisfaction with public services.